Finite element analysis of Invisalign®: one of a few removable appliances in orthodontic treatment - Hong, Qirong (2016)
People naturally would like to look good and having a great smile is one of them. Invisalign aids with the teeth correction to get that smile. However, dentists aren’t sure of have much pressure is being distributed onto the distorted teeth. Therefore, with this report, finite element method; with the means of ANSYS software, is used to identify the amount of force being exerted onto the teeth for correcting them to the desired perfect geometry that of the Dental Arch. During the modelling phase, the teeth is categorize as a rigid ceramic material with elasticity of 2*1011 while the more flexible aligner with elasticity of 4*1011 is assumed to behave like a beam element with additional features of linear springs incorporated along the cross section top view. The teeth are constrained as a fixed support while the aligner has its constraint along the mid-section where the pair of incisor coincides; allowing only movement in the y-direction to simulate symmetrical analyze since only half the teeth and aligner profile is considered in view of the amount of trials required for the project and to consider saving computational time. Single aligner and multiple aligners orthodontic treatment were simulated for evaluation. The difference in experiments is that only one aligner is used throughout the correction for the case on single aligner and several aligners of the same thickness for the case on multiple aligner with the addition of varying the starting correction position. The results extracted from ANSYS post-process to obtain the reaction force for both single and multiple aligners indicate similar observations. That the sets of experiment for both types concurs that with the increases in the amount of gaps away from the dental arch which is to be corrected with the aligners, the distributed loading follows a same pattern. The only difference was the magnitude of loading observed. Single aligner for all thickness tends to have a larger force exertion as compared to multiple aligners used for the same correction distance though this trending isn’t always the case for certain offset. It is also observed that the geometry for which the force is exerted on is different even though the same distance is covered. Since, the interaction between the two contacts is somewhat unpredictable, it is inconclusive to deem that the geometry has an impact to occurrences of the difference in magnitude. The author also made two assumptions in order at beginning to bring about such results. The first is to assume that the aligner has features of linear springs within on the basis of physical observation for that amount of elasticity. Since 3d modelling is too complex for modelling at this preliminary stage, it is taken that springs would be a good approximation to the 3d modelling. The other assumptions would be to limit the distance of offset to 0.00010m considering the facts that it would be impractical to stretch the aligner to such distance for correction and that it is damaging to the gum, when the journal by professor Heasman has shown that the one should not cross a value greater than 3N for brushing teeth and that it should be around 1.5 to 2N. For the lack of other references, the author took this value to demarcate a limit for correction and hence the above results. The author in addition found that approximately a set of 6 aligners, with a mixture of thickness 0.00105m and 0.00025m applied in the simulation, is able to effectively correct a teeth offset of 0.0020m. Future works could be to verify the works done by the author. Works can be either to perform practical experiments similar to that of the Rosetta strain gauge experiment to account for the force exertion or continue the analysis now with a three dimension model